The Implementation of Local Values in Aceh Education Curriculum - Abubakar, Abubakar; Aswita, Dian; Israwati, Israwati; Ferdianto, Jujuk; Jailani, Jailani; Anwar, Anwar; Ridhwan, Muhammad; Saputra, Didin Hadi; Hayati, Hayati (SCAD Independent, 2022)
This study aimed at finding the values ​​of local wisdom as well as strategies for transformation and internalization of these values ​​in the curriculum for students at Madrasah Tsanawiyah. This was qualitative research, and the sampling technique used was purposive sampling. Data collection was carried out using in-depth interview techniques, documentation, and strengthened by focus group discussions (consisting of 5 experts). The validity of the data was confirmed by the triangulation technique. The data were analyzed using inductive techniques to reveal the implicit/explicit meaning of the information in the field. The results of the study indicated that the value of learning needed to be adjusted to the character of the community. Characteristics of the Acehnese people who have a strong, reactive, and exocentric character, are more effective in learning through the use of symbols of local values. One of these local values ​​is peumalèe. Peumalèe can be explicitly implemented in the curriculum and implicitly embedded in the school curriculum. The value of peumalèe not only has a strong foundation in student learning because it is related to their daily beliefs and worship but also has social and religious sanctions for those who violate it.